Aspectos no contables que deben ser tomados en cuenta para la aprobación de créditos pyme por las entidades financieras de la región La Libertad - Florez Tolentino, Kevin Litman (2016)
The reality in which survive small and medium-sized enterprises of La Libertad region, where the poor accounting information that they have don't lend confidence in their reasonableness, requires users learn to identify other criteria that are useful for to determine accurately the real economic and financial situation of the entity, to interpret it and make prospectings. The research that has been conducted and presented in this work scientifically proves the existence of non-financial aspects that must be taken into account by financial institutions in the region La Libertad, when make financial analysis for credit approval to SMEs. This thesis has sampled 164 credits of total loans approved by financial institutions operating in the region La Libertad. Of which 124 loans have been granted to small enterprises and 40 loans to microenterprises, strategically distributed according to their geographical location and its proportion to the universe object of this study. The sample was calculated using a multistage probabilistic method. To testing the hypothesis, we used the logical and experimental model of "design with increased stimulation", for which several groups of loans approved, which served as experimental and control groups, so we apply the "no accounting standards" in different and gradual intensity to go analyzing the results magnitudes.